An evaluation of occlusal relationship and primate space in deciduous dentition in Kancheepuram District, Tamil Nadu, India - Daya Srinivasan; Divya Loganathan; S Saravana Kumar; C Joe Louis; Senthil Eagappan; Divya Natarajan (Wolters Kluwer Medknow Publications, 2017)
Aim: The objective of the study was to evaluate the occlusal characteristics of primary dentition in 3-5-year-old children in Kancheepuram district. Materials and Methods: A cross-sectional survey was carried out on children aged 3-5 year old in the Kancheepuram district. A total of 603 children were examined. Occlusal relationship was assessed separately on both right and left side and was classified as a flush terminal plane, mesial step, or distal step. Similarly, occlusal relationship of primary canine was examined and classified as Class I, II, or III. Primate space was measured in both the arches using digital Vernier caliper. Results: Pearson Chi-square test was used. Statistical significance was noted on both right and left side primary molar occlusion as well as in the canine occlusion across the three age groups. Primate spaces in both arches have been found to be significant across the three age groups. Mann-Whitney test between gender and occlusal relationship was found to be not significant. Conclusion: Flush terminal plane is the most common primary molar occlusion found in the present study which is statistically significant. Most of the children had primate space present in upper and lower teeth which is statistically significant.